Revealing the Community’s Interpretation of Place: Integrated Digital Support to Embed Photovoice Into Placemaking Processes - García-Esparza, Juan A. (2024)
Rising the quality of life through improving existing living environments remains one of the critical tasks of contemporary urban design. The quality of life is, in part, a subjective matter and shall thus be approached not only through professional measures but must also include participatory inputs. The techniques for including the residents’ points of view are various and greatly depend on the broader context of each case. However, using new ICT and other digitally supported tools is an ongoing trend and can be traced in various places and stages of the process. This article addresses the issue of the participatory reading of characteristics in existing living environments as they are assessed through residents’ eyes. It reviews and analyses two case studies, a Slovenian and a Spanish one, that used the photovoice approach with photography and related supplementary materials to get to know residents’ perceptions towards cultural and natural values that enhance their quality of life. The cases illustrate two different contexts, the urban and the rural one. In both cases, the processes were supported by a digital approach to achieve broader participation in the process, to offer residents an additional channel of expression, to analyse the input data, to disseminate the results, and to encourage a wider community and stakeholder dialogue. The case studies reflect the added value of using digital support in terms of the level of the integration of residents’ voices into the placemaking process. It concludes that the photovoice supported by digital tools can importantly enhance community-oriented urban planning processes.